Valor Nutritivo do Farelo de Linhaça em Ovinos - Fernandes, Danieli Perez (2010)
The objective was to evaluate this work through the intake and digestibility of linseed meal for sheep. A total of 12 female mongrel with body weight (BW) 30 kg were housed in cages for study of metabolism in the experimental period of 40 days (15 days for animal adaptation to experimental diets and 5 days for data collection in each phase). We used a randomized block design, to evaluate four diets (corn silage exclusively - SM, SM + concentrate; SM + concentrate + 5% linseed meal - FL, MS + concentrate + 10% FL) with three replications in two phases. A higher apparent digestibility of dry matter (DM) for calves fed concentrate diets, regardless of the proportion of linseed meal. The same effect was observed in the consumption of crude and digestible nutrients in kg / day, yet the inclusion of 10% linseed meal to the diet caused a decrease in consumption of about 138 g / day (gross nutrients) and 105 g / day ( digestible nutrients) compared to diet without linseed meal (0%). These results were very similar when expressed as% of BW and metabolic size (UTM (g/w0, 75). Inclusion of concentrate to the diet increases the digestibility of nutrients without detrimental effect of higher amount of linseed meal, However, this carries a slight decrease in DM. Therefore, we recommend using the diets containing concentrate and linseed meal in the proportions of 0 and 5%.